LncRNA TINCR Regulates Proliferation and Invasion of Hepatocellular Carcinoma Cells by Regulating the miR-375/ATG7 Axis. (16th September 2022) - Tang, Chengwu; Yu, Hongbin; Zheng, Yinyuan; Feng, Wenming; Shen, Jiasheng
Abstract : Purpose . The aim of this study was to examine the role of the long noncoding RNA (lncRNA) terminal differentiation-induced noncoding RNA (TINCR) on the proliferation, apoptosis, and invasion of liver cancer cells and its mechanism. Methods . The expression of lncRNA TINCR in twenty cases of liver cancer tissues, matched liver cancer cell lines, and paracancerous tissues was analyzed by RT-PCR. CCK-8, clonogenic test, flow cytometry, and Transwell assay were used to measure the effect of lncRNA TINCR overexpression and knockdown on cell proliferation, apoptosis, and invasion. Luciferase reporter and Western blotting showed that lncRNA TINCR regulates the expression of ATG7 through miR-375, and the rescue experiment proved that lncRNA TINCR controls the invasion and proliferation of liver cancer cells via the miR-375/ATG7 signaling pathway. Furthermore, in vivo nude mouse assay demonstrated that overexpression of lncRNA TINCR inhibited liver cancer cell growth. Results . The lncRNA TINCR was highly expressed in liver cancer tissues and cell lines. Liver cancer cells responded differently to knockdown of the lncRNA TINCR compared to overexpression in terms of proliferation, colony formation, and invasion. miR-375 negatively affected the expression of ATG7. The lncRNA TINCR bound to miR-375 and influenced its expression. Transfection of miR-375 mimics greatly inhibited the inhibitory effect of lncRNA TINCR knockdown on the invasion and proliferation, whereas transfection of miR-375 inhibitor considerably reverses this effect on liver cancer cells. Overexpressing lncRNA TINCR increased liver cancer cell proliferation in vivo. Conclusion . By controlling the miR-375/ATG7 axis, the lncRNA TINCR impacts the proliferation and invasion of liver cancer cells. Therefore, the lncRNA TINCR/miR-375/ATG7 signaling axis could be a novel biological target for the diagnosis and therapy of liver cancer.